PENGARUH BUDAYA ORGANISASI DAN PERAN KEPEMIMPINAN TERHADAP KNOWLEDGE SHARING - Dede Mustomi (Universitas Bina Sarana Informatika, 2017)
The background of this research about the effect organizational culture and leadership roles through knowledge sharing. Organizational culture is a common perception held by organization’s members (Robbins, 2005). Leadership roles are classified into eight types; monitor, coordinator, director, producer, innovator, broker, facilitator and mentor roles (Yang, 2007). Knowledge sharing as the action in which employees diffuse relevant information to others across the organization (Bartol dan Srivastava dalam Yang, 2007). The objectives of this research was to find out : (1) the influence of organizational culture toward knowledge sharing, (2) the influence of leadership roles toward knowledge sharing, (3) the influence of organizational culture and leadership roles toward knowledge sharing. This research uses survey method and questioners as the tools in collecting the main data. This research is conducted in PT. Pupuk Kujang, with respondent amount 130 personnel of employees. In this study, all variables were analysis with Multiple Regression. The results shows these following result : (1) there is a significant influence of organizational culture toward knowledge sharing, (2) there is a significant influence of leadership roles toward knowledge sharing, (3) there is a significant influence of organizational culture and leadership roles toward knowledge sharing.